Dracula doesn't drink lemonade / 16. - Dadey, Debbie (Dadey, Debbie. Adventures of the Bailey School kids, 1995)
The Bailey School kids' new guidance counselor, Mr. Drake, dresses in black, has an accent, chalky white skin, hands cold as ice, pointed teeth, and he hates bright light. Could he be the infamous king of the vampires?